Symptomatic cerebrospinal fluid HIV-1 escape in two patients on second-line antiretroviral therapy in Uganda. Issue 2 (16th February 2019) - Ssebambulidde, Kenneth; Segawa, Ivan; Laker, Eva; Lamorde, Mohammed; Castelnouvo, Barbara; Nakasujja, Noeline; Calcagno, Andrea
Abstract: Two HIV-infected individuals on second-line atazanavir-based antiretroviral therapy presented with neuropsychiatric symptoms. Cerebrospinal fluid HIV RNA was higher than plasma HIV RNA and antiretroviral regimens' optimization led to prompt resolution of symptoms in one. Patients on second-line atazanavir-based antiretroviral therapy with documented previous treatment failure may be at risk of symptomatic cerebrospinal fluid escape.